Participatory Research and Development for Sustainable Agriculture and Natural Resource Management : a Sourcebook Volume 2. - Gonsalves, Julian (International Development Research Centre, 2005)
Research and development can no longer be the exclusive domain of scientists. To find sustainable solutions to development problems, a wider range of actors must be involved. It is crucial, for example, that local stakeholders provide input to the process. Participatory research and development (PR & D) offers such an inclusive model. This three-volume sourcebook provides easy access to field-tested PR & D concepts and practices for practitioners, researchers, and academic. As well, it presents a comprehensive overview of PR & D and will serve as a general reference for trainers, policymakers, donor.